Predictive Factors of Blood Glucose Control among Pregnant Women with Gestational Diabetes Mellitus - Wongmak, Pornnipa; Phanpom, Chidchanok; Chaingta, Patchaneeya (Hua Hin Medical Journal, 2025)
Background: Gestational diabetes mellitus (GDM) is a complication that affects both the pregnant woman and the fetus. Many factors affect blood sugar control. The main goal of pregnancy care should be to control blood sugar levels within normal range to prevent complications. Objective: To examine the risk factors maternal age, pre-pregnancy body mass index (BMI), gestational weight gain, health literacy, and social support that contribute to elevated blood glucose levels among women with GDM. Method: This is a cross-sectional analytic study. Data were collected from 104 pregnant women diagnosed with GDM who attended antenatal care at Saraburi Hospital. Participants were categorized based on whether their blood glucose levels were within or above the recommended range. Data collection tools included a personal information questionnaire, a health literacy assessment, and a multidimensional perceived social support scale. Descriptive statistics and multivariable logistic regression were used for data analysis. Results: Women with gestational diabetes aged 30 years or older were 6.63 times more likely to have elevated blood glucose levels compared to those under 20 years (95% CI: 1.17–37.54, p=0.031). Additionally, those who experienced excessive gestational weight gain had a 3.18 times higher risk of elevated blood glucose compared to those with weight gain below the recommended level (95% CI: 1.19-8.48, p=0.021). Conclusion: Pregnant women with diabetes who are over 30 years old and gain an average of more than the standard weight per week during pregnancy are factors that affect blood sugar levels in pregnant women exceeding the standard. Therefore, nurses should give advice on changing their health care behavior to prevent complications.